Effects of different wavelengths of invasive laser acupuncture on chronic non-specific low back pain: a study protocol for a pilot randomized controlled trial - Jae-Hong Kim; Chang-Su Na; Gwang-Cheon Park; Jeong-Soon Lee (Trials, 2021)
Abstract Background Chronic non-specific low back pain (CLBP) is a common musculoskeletal disorder for which patients seek complementary and alternative medical treatments, including laser acupuncture (LA). Invasive LA (ILA) involves the simultaneous application of invasive acupuncture treatment at acupoints and focused laser irradiation. The efficacy of ILA for CLBP remains controversial owing to the insufficient clinical trial data. We intend to obtain basic data regarding the efficacy and safety of ILA for CLBP by comparing the effects of different wavelengths of ILA on CLBP. Methods This will be a prospective, patient-blinded, parallel-arm, single-center (DongShin University Gwangju Korean Medicine Hospital, Republic of Korea), pilot randomized controlled clinical trial. Forty-five participants with CLBP will be randomized in equal numbers into the control, 650-nm ILA (650 ILA), or 830-nm ILA (830 ILA) group. The control group will receive sham ILA for 10 min and real electroacupuncture (EA) for 10 min. The 650 and 830 ILA groups will receive real ILA (i.e., 650 ILA group, 650-nm wavelength; 830 ILA group, 830-nm wavelength) for 10 min and real EA for 10 min once/day, twice a week for 4 weeks, at bilateral Shenshu (BL23), Qihaishu (BL24), Dachangshu (BL25), and Huantiao (GB30). The primary outcome will be an improvement in pain intensity assessed using the visual analog scale. Scores in the Korean version of the Oswestry Disability Index and the European Quality of Life Five Dimension Five Level scale will be recorded as secondary outcome measures. All scores will be recorded at baseline (before intervention), 4 weeks after the first intervention (at the end of the intervention), and 4 weeks after completion of the intervention. Discussion The study is expected to provide preliminary evidence regarding the efficacy, safety, and usefulness of ILA for the treatment of CLBP. Trial registration This trial was registered with the Clinical Research Information Service (registration No. KCT0004610 ; http://cris.nih.go.kr ). Registered on 7 January 2020.